1993
DOI: 10.1148/radiology.186.1.8416562
|View full text |Cite
|
Sign up to set email alerts
|

Aortic regurgitation: quantitation with MR imaging velocity mapping.

Abstract: Aortic regurgitation (AR) in five healthy volunteers and 26 patients (mean age, 60.3 years; range, 25-83 years) was quantitatively measured with magnetic resonance (MR) imaging velocity mapping. Cine transverse images of the ascending aorta (32 phases per cardiac cycle) were acquired by using a gradient-echo sequence with a velocity-encoding bipolar pulse applied in the section-selection direction with a 1.5-T MR imaging unit. The aortic flow was calculated by integrating the product of area and mean velocity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
0
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(41 citation statements)
references
References 0 publications
2
37
0
1
Order By: Relevance
“…The rather qualita tive evaluation of the single slice technique contin ued using thinner slices (5 mm) in the ascending aorta showing small interobserver and intraob server variations in measuring the regurgitant frac tion (the ratio of the aortic regurgitant volume to the left ventricular stroke volume). The MR PVM results showed good correlation with those from volumetric MR measurements and parallel trends with echocardiographic or aortographic grading of aortic regurgitation [35]. Similarly good correlations between MR PVM results and volu metric MR results (r = 0.97 for the stroke volume) were found when the imaging slice was moved to the aortic valve level [36].…”
Section: Quantification Of the Aortic Regurgitant Volume With Mr Pvmsupporting
confidence: 55%
“…The rather qualita tive evaluation of the single slice technique contin ued using thinner slices (5 mm) in the ascending aorta showing small interobserver and intraob server variations in measuring the regurgitant frac tion (the ratio of the aortic regurgitant volume to the left ventricular stroke volume). The MR PVM results showed good correlation with those from volumetric MR measurements and parallel trends with echocardiographic or aortographic grading of aortic regurgitation [35]. Similarly good correlations between MR PVM results and volu metric MR results (r = 0.97 for the stroke volume) were found when the imaging slice was moved to the aortic valve level [36].…”
Section: Quantification Of the Aortic Regurgitant Volume With Mr Pvmsupporting
confidence: 55%
“…Early animal studies (6) also showed a good correlation between the flow rates measured with PVM and conventional flow meters. PVM measurements in humans correlated with conventional velocimetric techniques, such as Doppler ultrasound, and with other nonvelocimetric diagnostic techniques (2,(7)(8)(9)(10)(11)(12).…”
Section: Introductionmentioning
confidence: 85%
“…7,43,44 Early studies using CMR to evaluate valve regurgitation (aortic or mitral) focused on visualizing the signal void, with validations based on qualitative assessment or measurement of jet length or area compared with color Doppler or angiography (Tables 4 and 5). 45,[45][46][47][48][49][50][51][52][53][54][55][56][57][58] Evaluation of regurgitant severity based on jet area or length is no longer recommended, because this method is not a reliable indicator of disease severity. Nevertheless, visualization of distal flow disturbance by CMR, echocardiography, or angiography remains useful for detection of regurgitation and evaluation of jet direction and origin.…”
Section: Regurgitant Jet Areamentioning
confidence: 99%
“…Most adults with chronic valve regurgitation have significant regurgitation of only a single valve, which makes this approach widely applicable (Tables 4 and 5). [45][46][47][48][49][50][51][52][53][54][55][56][57][58] Phase contrast can directly quantify antegrade and retrograde flow volume across semilunar valves (Figures 4 and 5). To evaluate aortic regurgitation, phase-contrast imaging is performed in the aortic root, and total stroke volume and regurgitant volume are measured directly as the antegrade and retrograde transaortic volume flow rates.…”
Section: Regurgitant Volume and Fractionmentioning
confidence: 99%